Pengaruh Syari'ah Compliance Terhadap Market Share Bank syari'ah (Studi Kasus Perbankan Syari'ah Di Surakarta) - Tamalasari, Yenni; , Mutimatun Niami SH, M.Hum (2016)
An important pillar in the development of Islamic banks are Islamic principles (Sharia complience). Pilar which is the main differentiator anatar Islamic bank with conventional banks. Sharia supervision necessary to ensure teraplikasinya instituted the Islamic principles of banking, played by the Sharia Supervisory Board. Principles of Bank Indonesia research states that customers who use the services of Islamic banks, sebagain have a tendency to stop being customers, among others because of doubts or consistency in the application of sharia. Compliance and conformity to the principles of sharia Islamic banks often questioned by the customer. Implicitly it shows that the practice of Islamic banking has been less attention to the principles of sharia, one of the causes of the reputation and public confidence in the Islamic banks this will also have an impact on the loyalty of the community use the services of Islamic banks. Improved reputation and customer confidence can be used as an indicator of the success of the development of Islamic banks and Islamic banks as well the prediction of success in the future in order to increase market share.